The Effects of Murottal and Classical Music Combination toward Pregnant Women’s Anxiety in the 3rd Trimester - Rahayu Sumaningsih; Nurlailis Saadah; Budi Joko Santosa (Humanistic Network for Science and Technology (HNST), 2019)
Background: Pregnancy, give birth and breastfeeding process is a source of anxiety for pregnant women. Music therapy is considered as complementary therapy. The type of music that has medical purpose is Mozart’s classical music because it has a soft tone and stimulates alpha waves, calmness, and relaxation and nowadays Kitaro music to create relaxation. Methods: Research to distinguishing anxiety response and which type of music is more effective in reducing anxiety between murottal , Kitaro and combination music toward pregnant women’s 3rd trimester anxiety. This study quasi-experimental using pre-test post-test design. The sample size was 40 people divided into 4 groups. The independent variables include murottal, classical, combination and without music. The dependent variable is anxiety. It is carried out by looking for the mean before and after the intervention then analyzing by t-test and continued with the MANOVA. Results: Analysis of the combination music group p value 0.03 (p